2013
DOI: 10.1371/journal.pone.0074976
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection Synergizes with Three Inflammation-Related Genetic Variants in the GWASs to Increase Risk of Gastric Cancer in a Chinese Population

Abstract: BackgroundThree recent genome-wide association studies (GWASs) have reported that three SNPs (rs4072037, rs13361707 and rs2274223) located on genes related to host inflammatory response are significantly associated with susceptibility to gastric cancer (GC) in Chinese populations. Helicobacter pylori infection is also an important risk factor for GC through causing inflammatory response in the gastric mucosa. However, no study has established whether there are potential gene-environment interactions between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…On chromosome 5p13 all GC associated variants were in high LD ( r 2 > 0.8) to the most associated marker (rs6872282) and in high LD ( r 2 > 0.8) to all risk SNPs previously reported at this locus in Asians and Europeans . Thus, together with previous findings, our data provide evidence that one or more of these SNPs represent(s) the true GC conferring variant(s) in both the Asian and European population.…”
Section: Discussionsupporting
confidence: 82%
“…On chromosome 5p13 all GC associated variants were in high LD ( r 2 > 0.8) to the most associated marker (rs6872282) and in high LD ( r 2 > 0.8) to all risk SNPs previously reported at this locus in Asians and Europeans . Thus, together with previous findings, our data provide evidence that one or more of these SNPs represent(s) the true GC conferring variant(s) in both the Asian and European population.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have reported that the interaction between the genetic factors of a host and HP infection plays a significant role in gastric cancer carcinogenesis. The SNPs identified in previous studies were located on HP‐related genes ( IL‐1B, IL‐10, IL‐17, PGC, PTPN1, NOD1, NOD2 ), carcinogen detoxification‐related gene ( GSTP1 ), and cell proliferation‐related gene ( COX2 ) . In addition, DNA repair‐related genes, pattern‐recognition receptors, and genes identified in GWASs ( PSCA and MUC1 ) have important roles in gastric cancer carcinogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors that have been implicated include the following: cigarette smoking, H pylori infection, Epstein–Barr virus, radiation exposure, and prior gastric surgery for benign ulcer disease 18 . More recently, a number of investigators have shown that polymorphisms in inflammatory genes can be associated with gastric cancer risk 19, 20. Genetic risk factors include type A blood group, pernicious anemia, family history of gastric cancer, hereditary nonpolyposis colon cancer, and Li–Fraumeni syndrome 18 .…”
Section: Risk Factors For Gastric Cancermentioning
confidence: 99%